Trends in mean platelet volume and its relation with platelet count in patients with dengue fever - Naim, Fahad; Naeem, Awais; Nabi, Asif; Nizamuddin; Mehmood, Irum; Ullah, Sami (International Journal of Pathology, 2025)
Background: Dengue fever is an acute viral illness causes by a Flavivirus, called dengue virus. Worldwide, its affect about 350 million people yearly. It can cause serious complications like dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). This study aims to determine the role of mean platelets volume (MPV) in dengue patients and predict recovery.Methods: This Prospective observational study was conducted during 2021 dengue outbreak, starting from 20th August 2021 till 19th November 2021 at Medicine Unit, Khyber Teaching Hospital (KTH) Peshawar where a total of 276 patients of either gender who remained inpatients for at least 3 days and were afebrile on the day of discharge were enrolled using consecutive sampling technique. Prior ethical approval was taken. MPV was measured on the day of admission and discharge. Data was collected and analyzed using SPSS version 23.Results: In total 276 patients, 180 (65.2%) were males while 96 (34.8%) were females. Result reveals significant differences among hemoglobin value, hematocrit value, platelet count and mean platelet volume with p-values, 0.02, <0.001, 0.009 and <0.001 respectively. The results were also statistically significant at the time of admission and discharge among the three variables with p-value <0.001, <0.001 and 0.003 respectively.Conclusion: Dengue patients need constant monitoring to prevent complications predicts their recovery. This study concludes that MPV can be used as marker for dengue fever to determine the severity and/or improvement of patients.